Study of the effectiveness of vacuum-aspiration breast biopsy in patients with complete clinical response after neoadjuvant polychemotherapy in complex treatment of breast cancer - K. V. Maksimov; D. V. Bagdasarova; A. D. Zikiryakhodzhaev; A. A. Kolomeytseva; M. L. Mazo; V. S. Surkova; F. N. Usov; I. A. Eremeeva; A. N. Gerasimov (Исследования и практика в медицине)
Purpose of the study. Evaluation of the diagnostic value of vacuum-assisted biopsy (VAB) based on pathomorphological studies in patients with breast cancer (BC) who have achieved a complete clinical response (cCR) after neoadjuvant polychemotherapy (NACT).Patients and methods. In the study, conducted from 2021 to 2023 at the P. A. Hertsen Moscow Oncology Research Institute – a branch of the National Medical Research Radiology Center of the Ministry of Health of Russia, 35 patients with BC cT1–3N0–3M0 of various molecular-biological types who were diagnosed with cCR after NACT were included. All patients underwent VAB (needle size 7–10 G) of the breast followed by histological examination, after which surgical treatment was performed. Subsequently, histological conclusions of VAB and surgical materials were compared with each other for the presence and degree of pathomorphological response.Results. According to the pathomorphological conclusion when conducting VAB, the following results were obtained: 1 – true positive, 29 – true negative, 3 – false negative, and 0 – false positive. No statistically significant results of the association between complete pathomorphological response and the molecular-biological type of breast cancer were obtained (p > 0.05), however, there is a tendency towards the greatest number of complete pathomorphological responses in Her2-neu-positive (luminal – 100 %, non-luminal – 90.9 %) and triple-negative (87.50 %) types of breast cancer. The overall sensitivity of the method was 25.0 % (CI 6.8–60.2 %); specificity – 100 % (CI 88.1–100 %); false-negative result (presence of tumor cells in the surgical material and a negative result of VAB) – 9.1 % (CI 3.4–20.2 %); false-positive result (absence of tumor cells in the surgical material and a positive result of VAB) – 0 % (CI 0–10.6 %). The overall diagnostic accuracy of the method was 90.9 % (CI 79.8–96.6 %).Conclusion. The results of the conducted research allow for the consideration of excluding surgical treatment when a complete pathomorphological response is obtained by VAB. However, further research is required with the inclusion of a larger number of patients.